Love as the Warp and Weft of Creation: The Theological Aesthetics of Muhammad Iqbal and Rabindranath Tagore - Khalid Hina (Open Theology)
In this article, I explore in a comparative key the theological aesthetics of the celebrated poets Muhammad Iqbal (1877–1938) and Rabindranath Tagore (1861–1941). For both figures, I argue, human artistry reflects as well as instantiates the primordial divine creativity. I begin by exploring the foundational metaphysics of Iqbal and Tagore, wherein the finite world stands as a shimmering sign of the inexhaustible infinite. Within this cosmic tapestry, the divine and the human are dynamically bound in a co-creative and loving relationality. In this spiralling structure of reciprocity, art, for both of our poets, enables us to see the divine light and hear the divine call anew, and thus situates us ever more firmly in the finite world – a world which is always, in the Iqbalian and Tagorean worldviews, brimming over with the infinite.